The Effect of Brand Experience on Brand Loyalty in Indonesian automotive Industry: The Mediating Role of Customer Satisfaction and Brand Trust - Putra cahya wijaya; Ananda Sabil Hussein; Agung Yuniarinto (Journal of Business and Management Review, 2022)
The automotive industry is one of the mainstay sectors of national economic growth in Indonesia and the performance of this automotive industry sector always grows and leads in a positive direction every year making business competition dynamic and competitive. Marketers in the automotive industry need to try to increase brand loyalty to get customer repurchase intention and word of mouth. Customer repurchase intention is very important for business continuity in every company and word of mouth as a powerful marketing strategy to increase brand trust which has an impact on increasing sales. Customer satisfaction is an aspect that can create repurchase intention, while brand trust will increase customer word of mouth. The right strategy to achieve customer satisfaction and brand trust is to create a positive brand experience for customers. This research aims to determine the effect of brand experience on brand loyalty directly and indirectly through customer satisfaction and brand trust on Toyota brand car customers in Madiun. This type of research approach uses quantitative descriptive analysis with explanatory research methods and the sample technique uses random sampling, with a total sample of 200 respondents and the determination of the number of samples in this study using purposive sampling technique. The data collection method used a questionnaire and the data was analyzed by SEM-PLS using smartPLS3 software. The findings of this research indicate that brand experience does not have a significant effect on brand loyalty directly. Meanwhile, customer satisfaction and brand trust are able to perfectly mediate the relationship between brand experience and brand loyalty.